Athlete branding Edgar Xavier Marvelo as an Indonesian wushu athlete on Instagram - Christiani, Monica; Hafiar, Hanny; Anisa, Renata (Manajemen Komunikasi, 2023)
The popularity of the sports world expanded athletes’ role experience, where athletes who were previously only doing sports things developed into public figures and were involved in social and business activities. The expansion of this role puts athletes into the public spotlight, which makes them need to have credibility. Therefore, athlete branding is important to be developed to form a good image and can attract the public and get opportunities for collaboration. Edgar Xavier Marvelo, an Indonesian national wushu athlete with worldwide achievements, has carried out athlete branding activities on Instagram. This study uses the model of athlete brand image from Akiko Arai, Yong Jae Ko, and Stephen Ross to know the athletic performance, attractive appearance, and marketable lifestyle of Edgar Xavier Marvelo’s athlete branding as an Indonesian wushu athlete on Instagram. This qualitative descriptive study uses data collection techniques through observation, interviews, literature study, and online searches. This study shows that Edgar Xavier Marvelo has carried out athlete branding activities on Instagram according to the dimensions of the Model of the Athlete Brand Image. However, its athletic performance, attractive appearance, and marketable lifestyle have not been implemented consistently. Suggestions from this research, he can upload his wushu skills and competition style. Symbols also need to be formed and uploaded more about physical attractiveness and body fitness. Uploads about social life also need to be added to show the role model side. He needs to upload consistently, strategize content, and learn the Instagram algorithm to increase engagement.